Manajemen Fisioterapi pada Kasus Post-Operative Fraktur Supracondylar Humerus: Studi Kasus - Bintari, Nur Juniarti; Fatmarizka, Tiara; Pradana, Anas (Prosiding University Research Colloquium, 2023)
Supracondylar fracture of the humerus is the most common elbow fracture in children and usually occur in children between the ages of 5 and 7 years. Limitation of joint mobility is a common complication after surgery in the elbow area. In the patient Mr. E.M.W with a diagnosis of post open reduction internal fixation in a complete fracture of the left supracondylar humerus found movement pain problems, ROM limitations, decreased muscle strength and decreased function of the upper extremities. Physiotherapy interventions that given to patient such as infrared, muscle energy techniques, and active ROM exercise provide good changes such as decreased pain levels, increased left elbow flexion and extension ROM in both active and passive motion, and increased upper extremity function. For the left elbow flexor and extensor muscle groups that experienced a decrease in strength, there was no increase in muscle strength which could be due to the lack of frequency of physiotherapy sessions.